Principles and Practical Methods for Preventing Sports Injuries in Fitness Activities - Zheng, Xuanzhuo (International Journal of Public Health and Medical Research, 2026)
Against the backdrop of the deepening of the national fitness strategy, the enthusiasm for participation in public fitness continues to rise, and the size of the sports population is expanding year by year. However, the problem of sports injuries is also becoming increasingly prominent, which not only affects the continuity of fitness plans, but some acute injuries may also cause irreversible joint function impairment, becoming an important obstacle to the high-quality development of national fitness. Based on the clinical practice results and authoritative monitoring data of sports medicine, this article clarifies the core principles of sports injury prevention in fitness activities, systematically sorts out the practical paths of key dimensions such as individual adaptation assessment, scientific exercise planning, and standardized technical execution, and addresses the differentiated protection needs of the ordinary fitness population and special populations such as the elderly and those with chronic diseases. Related studies have confirmed that strict implementation of scientific prevention measures can reduce the incidence of fitness-related sports injuries by over 40%. The research results of this article aim to provide practical preventive guidance for the fitness population and professional instructors, as well as provide reference for fitness institutions to develop safety training standards, and facilitate the safe and effective development of national fitness activities.